Adaptive speckle filtering for real-time computing in low earth orbit satellite synthetic aperture radar - Kim, Kyeongrok; Jung, Soyi; Kim, Jae Hyun (ICT Express, 2021)
As the number of low Earth orbit satellites is increasing, new algorithms and high-performance computing resources are needed to handle the enormous real-time arrival data generated by satellites. Based on the requirements, this paper proposes a novel real-time adaptive speckle filtering selection algorithm for satellite synthetic aperture radar (SAR) images. The use of high-performance filters generates high-quality images whereas it introduces delays. Thus, a real-time adaptive algorithm which achieves time-average SAR image quality maximization subject to delays using Lyapunov optimization, where the delay is formulated with a queuing model. Evaluation results show that the proposed algorithm guarantees desired performance improvements.
Keywords: Adaptive filtering; Low earth orbit (LEO) satellite; Speckle filtering; Synthetic aperture radar (SAR)